Pengaruh organizational identification terhadap employees innovative work behavior melalui employee engagement sebagai variabel mediasi dan creative self-efficacy sebagai variabel moderasi pada karyawan start-up di Jakarta - Jayapradesta, Jordi; Firdausy, Carunia Mulya (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This research aims to examine the influence of organizational identification on employees’ innovative work behavior through employee engagement as a mediating variable and creative self-efficacy as a moderating variable in start-up employees in Jakarta. Five hypotheses were developed according to the number of independent variables with mediation and moderation. The number sample of respondents in this study was 92 employees who worked at start-up companies in Jakarta. The method used to analyze the data was by applying PLS-SEM. The results show that organizational identification influences employee engagement at start-up companies in Jakarta. Also, employee engagement influences employees’ innovative work behavior at start-up companies in Jakarta. Organizational identification influences employee innovative work behavior in start-up companies in Jakarta. Organizational identification influences employee innovative work behavior through employee engagement in start-up companies in Jakarta, and creative self-efficacy moderates the influence of employee engagement on employees’ innovativeness work behavior at start-up companies in Jakarta. Therefore, start-up companies in Jakarta need to evaluate the level of employee engagement at work, to start implementing education and training for companies regarding the importance of recognition and attachment to the company and how the added value of innovative behavior in employees, as well as to further pay attention to the level of employee engagement by paying attention to determining factors such as employee psychological factors so that you can identify the characteristics of employees who have high employee engagement. Penelitian ini bertujuan untuk melihat pengaruh organizational identification terhadap employees’ innovative work behavior melalui employee engagement sebagai variabel mediasi dan creative self-efficacy sebagai variabel moderasi pada karyawan start-up di Jakarta. Dikembangkan 5 hipotesis sesuai dengan banyaknya variabel bebas dengan mediasi dan moderasi. Sampel dalam penelitian ini adalah 92 karyawan yang bekerja di perusahaan start-up di Jakarta. Untuk mengolah data-datanya, peneliti menggunakan program SmartPLS untuk uji validitas dan reliabilitas serta pengolahan data, diperoleh kesimpulan bahwa organizational identification berpengaruh terhadap employee engagement karyawan pada perusahaan start-up di Jakarta, employee engagement berpengaruh terhadap employees’ innovative work behavior karyawan pada perusahaan start-up di Jakarta, organizational identification berpengaruh terhadap employees’ innovative work behavior karyawan pada perusahaan start-up di Jakarta, organizational identification berpengaruh terhadap employees’ innovative work behavior karyawan melalui employee engagement pada perusahaan start-up di Jakarta, dan creative self-efficacy memoderasi pengaruh employee engagement terhadap employees’ innovative work behavior karyawan pada perusahaan start-up di Jakarta. Kontribusi penelitian ini sangat disarankan kepada para pihak perusahaan start-up di Jakarta untuk mengevaluasi tingkat engagement karyawan yang bekerja, untuk mulai menerapkan edukasi dan training kepada perusahaan mengenai pentingnya pengenalan dan keterikatan terhadap perusahaan serta bagaimana nilai lebih dari perilaku inovatif pada karyawan, serta untuk lebih memerhatikan tingkat keterikatan karyawan dengan cara memerhatikan faktor-faktor yang menentukan seperti faktor psikologis karyawan agar dapat diketahui ciri-ciri karyawan yang memiliki keterikatan kerja tinggi.